FIGURATIVE LANGUAGES IN THE NOVEL THE ADVENTURE OF TOM SAWYER BY MARK TWAIN - Dita Ainul Nirmawati; Vera Kristiana (Fakultas Sastra UMN AL Washliyah, 2022)
Language was the medium of communication by which people can maintain their social relationships. It was impossible for people to live without socializing with others. Literature had many types in our daily life. Such as drama, novel, poetry, and novel. Language of literature worked had aesthetic element because literature was built by words. The figurative language had the implied meaning or we can say that the meaning of the figurative language was based on the context. Based on the results of the analysis in the novel “The Adventures of Tom Sawyer” by Mark Twain, the researcher can conclude that it was found 10 types of figurative language in the novel. The result of this analysis showed that there were 10 types of figurative languages found in this novel were; simile, personification, metaphor, synecdoche, allegory, paradox, metonymy, hyperbole, symbol, understatement, and irony. The type of figurative language that did not existed in this novel was the apostrophe. The types of figurative language personification and hyperbole were dominantly used in this novel, the author wants to made the reader not bored reading the novel and to make the readers know clearly the character of the existing characters in the novel. By using hyperbole readers can clarified the character or personality of the characters. The researcher proposed suggestions for the readers and literary enthusiasts were able to understanded the study of figurative language in particular used of language as a tool for communication.